THE INFLUENCE OF SOCIAL SUPPORT TOWARDS COMPETITIVE ANXIETY IN GAREC’S SSB STUDENTS - Patricia Lunanta, Lita; Darmawan Rahardi, Ananda; Siwi Respati, Winanti; Rahmana, Arief (International Journal of Psychosocial Rehabilitation, 2020)
SSB Garec’s is one of the oldest SSBs in Jakarta, demands students to have a positive impact on the students’ attitude and they will be able to gain achievements, but other impacts will arise when students compete anxiety because of the demands they face. This is due to the lack of social support received by students hence the impact of the demands cause competition anxiety. The purpose of this study is to investigate the effect of social support on anxiety in competing SSB Garec’s students. This research is quantitative, using the Regression method with a sampling technique in the form of purposive sampling. The number of research samples were 60 SSB Garec’s students. The social support scale based on the theory of Sarafino (2002) uses the Galuh scale (2015) which has been adapted and modified, this item amounts to 32 valid items with a reliability coefficient (α) of 0.932. Competitive Anxiety Scale based on Cox’s theory (2012) this scale is constructed based on the dimensions of Competitive Anxiety Martens (in Cox, 2012) this item is 26 valid items with a reliability coefficient (α) of 0.945. The results showed p = 0,000 with a coefficient of -0.440, meaning that the hypothesis was accepted that there was a negative influence of social support on anxiety competing against Garec’s SSB students. Based on the value of R 2 indicates social support contributed by 41.1% in the anxiety affect play, while 59.9% are influenced by other factors.